2021
DOI: 10.2169/internalmedicine.6784-20
|View full text |Cite
|
Sign up to set email alerts
|

Association between Changes in the Systolic Blood Pressure from Evening to the Next Morning and Night Glucose Variability in Heart Disease Patients

Abstract: Aims To assess the impact of glycemic variability on blood pressure in hospitalized patients with cardiac disease. Methods In 40 patients with cardiovascular disease, the glucose levels were monitored by flash continuous glucose monitoring (FGM; Free-Style Libre™ or Free-Style Libre Pro; Abbott, Witney, Oxfordshire, UK) and self-monitoring blood glucose (SMBG) for 14 days. Blood pressure measurements were performed twice daily (morning and evening) at the same time as the glucose level measurement using SMBG. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…One study used the DexCom G4 Platinum technology [ 28 ] whereas seven studies used Medtronic glucose sensors [ 21 , 23 , 25 , 27 , 29 , 31 , 32 ]. One study used an intermittently scanned CGM device (using flash technology—FGM) for 14 days [ 30 ]. Regarding the BP assessment methodology, seven studies used ambulatory BP monitoring (ABPM) for the assessment of the participants’ BP profiles [ 20 , 24 , 25 , 27 , 28 , 31 , 32 ].…”
Section: Presentation Of the Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One study used the DexCom G4 Platinum technology [ 28 ] whereas seven studies used Medtronic glucose sensors [ 21 , 23 , 25 , 27 , 29 , 31 , 32 ]. One study used an intermittently scanned CGM device (using flash technology—FGM) for 14 days [ 30 ]. Regarding the BP assessment methodology, seven studies used ambulatory BP monitoring (ABPM) for the assessment of the participants’ BP profiles [ 20 , 24 , 25 , 27 , 28 , 31 , 32 ].…”
Section: Presentation Of the Resultsmentioning
confidence: 99%
“…Regarding the BP assessment methodology, seven studies used ambulatory BP monitoring (ABPM) for the assessment of the participants’ BP profiles [ 20 , 24 , 25 , 27 , 28 , 31 , 32 ]. Five studies used office BP measurements [ 21 , 22 , 26 , 29 , 30 ], most of them with a significant lack of details, and a single study reported the use of self-measurements [ 23 ].…”
Section: Presentation Of the Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The group with an MEdif of ≥20 mm Hg had higher stroke incidence and CVD events compared to the group with an MEdif <20 mm Hg [4,11]. Similar to nocturnal hypoxia, MEdif was also significantly associated with markers of subclinical CVD and cardiac damage parameters such as total cholesterol levels [12], night glucose variability [13], left ventricular hypertrophy, relative wall thickness and left ventricular diastolic dysfunction [14,15] among hypertensive patients. Available evidence has shown that the cutoff value of 20 mm Hg is a potential threshold for clinical MEdif.…”
mentioning
confidence: 91%